A PRACTICAL APPROACH FOR MOBILE-BASED REMOTE CONTROL - Al Mghawish, Afif Jadalla (European Scientific Journal, ESJ, 2013)
﻿Nowadays, the increasing role of advanced electronic Systems, Mobile networks, wireless communications and digital technologies affects many methods used in remotely controlled Systems. One of these methods is the mobile –based control system design and analysis, which is practical and applicable in read-time development. This paper suggests a new remote control technique based on mobile capabilities to control a driving motor circuit which in turn will monitor and control the direction of the dc-motor. The proposed system can generate a control signal through a Global system for mobile communications (GSM) modem either by SMS or Dual Tone Multi-Frequencies (DTMF) techniques to drive the dc- motor movement s. An experimental study was done and the obtained result showed the effectiveness of the proposed method .